EKSPERIMENTASI MODEL PEMBELAJARAN TEACHING GAME TEAM TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA DITINJAU DARI KEMAMPUAN AWAL SISWA KELAS IXSMP NEGERI 14 MERANGIN - Istiqomah; Hidayati Rais; Hasmawati Hasmawati (Matedukasia, 2023)
This research aims to determine and describe students' understanding of mathematical concepts through the application of the Teaching Game Team learning model. The research population was class IX students. This research uses a quasi-experimental method with a 2x3 factorial design involving 2 sample classes. Sampling used a random sampling technique with a sample of 48 students. The data collection technique uses test questions describing the ability to understand concepts in terms of students' initial abilities. Testing hypotheses 1, 2, 3 and 4 uses the t-test formula and hypothesis 5 uses the two-way Anova technique. Based on the results of the hypothesis test, it was found that hypothesis 1 was accepted, where students' overall understanding of mathematical concepts using the teaching game team learning model was better than conventional learning. Meanwhile, Hypotheses 2, 3 and 4 are rejected, meaning that the understanding of mathematical concepts for those with high, medium and low initial abilities using the teaching game team learning model is no better.or equal to conventional learning. Hypothesis 5 is rejected, so there is no interaction between the teaching game team learning model in terms of initial ability to influence understanding of mathematical concepts.